PENGARUH SOSIALISASI, PENGETAHUAN, SANKSI DAN KUALITAS PELAYANAN PADA KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR - Lisa Rusmayani, Ni Made; Supadmi, Ni Luh (E-Jurnal Akuntansi; Vol 20 No 1 (2017), 2017)
ABSTRACT Vehicle tax compliance in Tabanan has an important role to increase local revenue. Data arrears vehicle tax at SAMSAT Tabanan on 2011-2015 proving that there is still taxpayer that less obedient to completed their tax liabilities. This research purpose to knowing the effect of socialization of taxation, tax knowledge, tax pinalties, and service quality to vehicle  tax compliance. The method of collecting data at this research is using the survey method with questionnaire instrument. The samples used of 100 respondents was calculated based on the formula slovin of sampling accsidental.  The data analysis technique used in this research is multiple linear regression. Based on the analysis, this study showed that the socialization of taxation, tax knowledge, tax penalties and service quality positive and significant impact on taxpayer compliance in paying vehicles tax in SAMSAT Tabanan. Keywords: tax compliance, socialization, knowledge, pinalties, service quality.
Keywords: tax compliance, socialization, knowledge, pinalties, service quality